Disentangling motivation and engagement: Exploring the role of effort in promoting greater conceptual and methodological clarity - Nagy, Robin P.; Martin, Andrew J.; Collie, Rebecca J. (Frontiers in Psychology, 2022)
Motivation and engagement are often conflated by researchers and practitioners, impeding research and practice aimed at optimizing students’ academic development. One reason for this is because definition and measurement are often too general or diffuse—especially in the case of engagement. More conceptual and psychometric precision is needed—again, particularly in the case of engagement. To the extent that engagement is inadequately understood and assessed, motivation research that involves engagement is hampered. The present study seeks to bring greater clarity to this space through a purposeful focus on effort (a specific facet under the engagement umbrella) and how it relates to multidimensional motivation. Drawing on data from a sample of 946 Australian high school students in 59 mathematics classrooms at 5 schools, this study hypothesized a tripartite model of academic effort in terms of operative, cognitive, and social-emotional dimensions. A novel nine-item self-report Effort Scale that measures each of the three effort factors was developed and tested for internal and external validity—including its relationship with multidimensional motivation. Results of multilevel (students at Level 1; classrooms at Level 2) confirmatory factor analysis supported the hypothesized model of tripartite effort and its distinctiveness from motivation. Multilevel doubly-latent structural equation modelling then explored the process of motivation → engagement (effort), showing that key dimensions of motivation predicted effort at student- and classroom-levels. Taken together, the findings show that bringing conceptual and psychometric clarity to effort is not only critical for better understanding engagement, but also for validly differentiating engagement from motivation—and in turn, better understanding motivation itself.